In vitro screening for Antimycotic Activity of Various Extracts of Centratherum anthelminticum Seeds by the Microtiter Plate Based Assay - Patel, Dr. Vipul P (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTPlants are the natural and traditional source of the drug. Investigations were carried out to evaluate the anti mycotic properties of the various extract of the seeds of Kalijiri (Centratherum Anthelminticum). The dried fruits were successively extracted with ethanol, petroleum ether, hexane, chloroform, diethyl ether using Soxhlet Apparatus. All the extracts and powdered drug were screened for its antimycotic activity using Microtiter plate based assay method by the CLSI (Previously NCCLS) protocol M27 – A2. Amphotericin B was used as a standard drug as a positive control. IC50 value was calculated using the software Graphpad Prism ver. 5.0. During study we found that Ethanolic extract showed most potent activity against Candida tropicalis and Candida parapsilosis while chloroform extract, N-Hexane extract, Diethyl ether and petroleum ether extract. Ethanolic extract have also shown significant activity against Aspergillus fumigatus, Issatchenkia orientalis, and Candida albicans. Chloroform extract shown potent activity against Aspergillus fumigates and less potent activity against Candida Albicans, Candida parapsilosis, Candida tropicalis and Issatchenkia orientalis. Diethyl ether, N-Hexane extract and petroleum ether extract have not shown significant activity against any fungal strains. Further study should be done with separated and purified phytochemical constituent which is responsible for antimycotic activity of the extract.